MACEDONIAN TRANSLATION EQUIVALENTS OF THE ENGLISH GET-PASSIVE (Journal of Contemporary Philology, 2023)
This paper deals with the English get-passive construction and its possible translation equivalents in Macedonian. The aim of the research is to investigate which constructions in Macedonian can be used as functional equivalents to the English get-passive.This research is based on a database of 180 parallel examples created by the authors, searching translations in both directions, English-Macedonian and Macedonian-English. A qualitative and quantitative analysis of the collected data was conducted with an aim to establish a correlation between the English get-passive and its Macedonian equivalents. By determining the similarities and differences between the English get-passive and the Macedonian passive constructions (the periphrastic and the reflexive passive) we assumed that there is no full correspondence, thus a wider variety of structures were expected in the Macedonian counterpart examples. Consequently the distribution of the equivalent Macedonian structures will hopefully give some insight both into the nature of the English get-passive and the scarcely studied Macedonian passive constructions as well as relevant guidelines for translators and teachers.
Keywords: voice; contrastive analysis; periphrastic passive; reflexive; middle